Corporate Reputation of Higher Educational Institution (HEI): A Study of Selected Universities in Lagos State, Nigeria (Lapai Journal of Economics, 2024)
The focus of this study was to examine the effect of corporate reputation in selected Universities in Lagos State. Specifically, it examined how service quality impacted on academic programmes, identified effects of student satisfaction on the retention rates and also investigated the effects of public perception on graduation and employment opportunities among selected Universities in Lagos State, Nigeria. It further conceptualized the variables used and employed Institutional Theory as the basis of the theoretical framework. The study reveals significant effects between quality of services and academic programs of the selected Universities in Lagos State. Also, student satisfaction significantly influence retention rate of selected Universities in Lagos State. Likewise, Public perception significantly influenced the graduation and employment opportunities of selected Universities in Lagos State. The study however recommended that to leverage public perception for better graduation and employment outcomes, Universities should invest in enhancing their academic programs, improving career services, and actively promoting the success of their students and alumni.